2009
DOI: 10.1148/radiol.2533090303
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Measurements in Patients with Asthma: Comparison of Quantitative Thin-Section CT Findings with Those in Healthy Subjects and Correlation with Pathologic Findings

Abstract: Axial reconstructions with orthogonal measurements along the airways enabled by three-dimensional segmentation methods are able to demonstrate significant changes in bronchial morphometry, predicting airflow limitation in asthma, and may have a role in the noninvasive measurement of airway remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 38 publications
(64 reference statements)
9
86
1
2
Order By: Relevance
“…In cases of asthma, there was a strong trend for the mean lower asymptote of the PL-Ai curve (constant a of the Venegas equation 5 Ai when the airway is fully deflated) to be less than in the control group (P 5 0.06), and this was statistically significant in the subgroup with more severe asthma (P 5 0.006) ( Table 4, Figure 4, Table E2). Some studies have also reported smaller airway caliber in patients with asthma (10,31,32), although others have observed minimal change (33,34). Potential mechanisms for a smaller airway size include encroachment on the lumen by thickened airway walls, reduced tethering from surrounding parenchyma, or possibly increased smooth muscle contractility (although the latter is unlikely in this study).…”
Section: Elastic Properties In Obstructive Lung Diseasementioning
confidence: 59%
“…In cases of asthma, there was a strong trend for the mean lower asymptote of the PL-Ai curve (constant a of the Venegas equation 5 Ai when the airway is fully deflated) to be less than in the control group (P 5 0.06), and this was statistically significant in the subgroup with more severe asthma (P 5 0.006) ( Table 4, Figure 4, Table E2). Some studies have also reported smaller airway caliber in patients with asthma (10,31,32), although others have observed minimal change (33,34). Potential mechanisms for a smaller airway size include encroachment on the lumen by thickened airway walls, reduced tethering from surrounding parenchyma, or possibly increased smooth muscle contractility (although the latter is unlikely in this study).…”
Section: Elastic Properties In Obstructive Lung Diseasementioning
confidence: 59%
“…Some pathologies affect the tree structure; in asthma for instance, airways can be constricted. This goes from frequent moderate constrictions throughout the tree with airway radii reductions of 10 to 25% on average [18], [2] up to, in a low proportion of cases, complete closure [10], [8]. These latter severe constrictions will be designated as plugs.…”
Section: Global Methodologymentioning
confidence: 99%
“…The pressure drop and the flow in an airway are linked through a non linear coefficient ( ) , called resistance, by = ( ) . This coefficient is defined as in [21] by the Pedley model [22]: Remark 1: note that equation (2) has been designed for inspiration and for one bifurcation angle only.…”
Section: Direct Ventilation Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…2a and b). By using this technique in asthmatic patients, it has been shown that the strongest correlation with airflow obstruction was found through airway wall measurements of the more distal airways [66]. Although current evidence indicates that small airways obstruction could be routinely assessed using CT scanning, this technique does have some limitations, including lack of standardization of the technical parameters of the CT scanner, lack of consensus on the best index for small-airways disease assessment, and exposure of subjects to ionizing radiation.…”
Section: Imaging Assessment Of Peripheral Airwaysmentioning
confidence: 99%